El desarrollo de la competencia gramatical a través de la retroalimentación correctiva directa con los estudiantes de noveno a en la unidad educativa José Angel Palacio de la ciudad de Loja durante el año escolar 2016-2017 - Juncay Guanuche, Monica Rocio (2018)
The aim of this research work was to develop grammatical competence through direct corrective feedback with the ninth year A students at Unidad Educativa José Ángel Palacio during the academic year 2016-2017. The analytical-synthetic, statistical, scientific and descriptive methods were used to analyze, and process information. The instruments used to collect the data were observation sheets, tests, and questionnaires, applied to 29 students. The results indicated that students increased their grammatical competence knowledge to an average level by being able to use grammatical structures easily, asking questions and answering them in short or long forms, to recognize the subject verb agreement, and differentiate the parts of speech. In conclusion, the use of direct corrective feedback improved notably student’s grammatical competence, allowed them to express their own ideas, understood others and feel more confident to participate actively and to have good performance in all activities developed in class.